2015
DOI: 10.1371/journal.pone.0124499
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Genotype Diversity of Anal HPV Infection among MSM in Northern Thailand

Abstract: BackgroundHPV infection is common and may cause cancer among men who have sex with men (MSM). Anal HPV infection (HPV+) was found in 85% of HIV-positive (HIV+) and 59% of HIV-negative (HIV-) MSM in Bangkok, central Thailand. As little is known about HPV in this group in northern Thailand, we studied MSM subgroups comprised of gay men (GM), bisexual men (BM), and transgender women (TGW).MethodsFrom July 2012 through January 2013, 85 (42.5% of 200) GM, 30 (15%) BM, and 85 (42.5%) TGW who practiced receptive anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
6
27
0
Order By: Relevance
“…In this study, the single most frequently detected type was HPV-58 (30.2%) in HIV-infected MSM. Supindham et al recently reported that HPV-58 infection rate was 29% in HIV-infected MSM in Northern Thailand [ 32 ], which is quite similar to the rate in our study. They also showed a lower rate of HPV-58 (18%) in non-HIV-infected MSM compared with HIV-infected MSM [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the single most frequently detected type was HPV-58 (30.2%) in HIV-infected MSM. Supindham et al recently reported that HPV-58 infection rate was 29% in HIV-infected MSM in Northern Thailand [ 32 ], which is quite similar to the rate in our study. They also showed a lower rate of HPV-58 (18%) in non-HIV-infected MSM compared with HIV-infected MSM [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Supindham et al recently reported that HPV-58 infection rate was 29% in HIV-infected MSM in Northern Thailand [ 32 ], which is quite similar to the rate in our study. They also showed a lower rate of HPV-58 (18%) in non-HIV-infected MSM compared with HIV-infected MSM [ 32 ]. In another study in Bangkok, Phanuphak et al reported that the HPV-58 infection rate was significantly higher in HIV-positive MSM (10.8%) than in HIV-negative MSM (4.9%) [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among over 40 types of HPV, at least 13 are considered high risk with respect to their carcinogenic potential (22).…”
Section: Human Papillomavirus Infectionsmentioning
confidence: 99%
“…A number of studies of both transgender and nontransgender people indicate that HPV and HPV-related anal squamous intraepithelial lesions are more common in human immunodeficiency virus-infected individuals (22,27,28). Human immunodeficiency virus infections are common among transgender people, particularly transwomen who have some of the highest laboratory-confirmed prevalence estimates in the world (29).…”
Section: Human Papillomavirus Infectionsmentioning
confidence: 99%
“…Men and women with HIV infection show an increased risk and rate of HPV acquisition and persistence, frequent carriage of multiple HPV types, and an increased risk of HPV‐related disease including rapidly progressive malignancies . HPV carriage rates and overall disease risk increase at low CD4 cell counts.…”
Section: Human Papilloma Virusmentioning
confidence: 99%